Teaching Strategies for Counteracting Chinese Vocabulary Attrition Based on Dynamic Systems Theory - Qiuijang , Li; Zhenping, Liu (Journal of Roi Kaensarn Academi, 2024)
Grounded in Dynamic Systems Theory (DST), this study investigates strategies to mitigate Chinese vocabulary attrition among Thai Chinese learners. DST highlights the non-linear and dynamic nature of language learning, offering a framework to analyze the interplay between emotional motivation, language exposure, and personalized strategies in vocabulary retention. Vocabulary attrition, common among language learners, often results from insufficient use, lack of reinforcement, or emotional disengagement. Thai Chinese learners face unique challenges stemming from linguistic and cultural differences, necessitating targeted interventions to address these factors. This study identifies three key strategies: emotional encouragement, personalized revision, and diversified exposure, which enhance emotional connections, increase reinforcement frequency, and adapt to learners’ needs. Findings reveal that emotional encouragement and diversified exposure significantly improve retention, while personalized revision supports learners at varying proficiency levels. Advanced learners benefit from self-directed review, while less proficient learners require structured, frequent exposure to stabilize retention. These insights highlight the importance of integrating DST with practical strategies to reduce vocabulary attrition, providing actionable guidance for educators and a basis for further research on cultural integration and advanced teaching tools.